2009
DOI: 10.1038/jid.2008.317
|View full text |Cite
|
Sign up to set email alerts
|

High β-HPV DNA Loads and Strong Seroreactivity Are Present in Epidermodysplasia Verruciformis

Abstract: Epidermodysplasia verruciformis (EV) is a rare disease, characterized by cutaneous warts and associated with a strong predisposition to beta-genus human papillomavirus (HPV). Earlier studies reported high copy numbers of HPV-DNA in nearly all skin tumors from EV patients, but neither HPV replication status in non-lesional skin nor anti-HPV seroreactivity in these patients have been reported yet. We therefore performed a comprehensive viral load analysis for the more common beta-HPV types on skin samples and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 44 publications
6
72
0
4
Order By: Relevance
“…In addition, we have also demonstrated, using fluorescent in situ hybridization (FISH), that the abundance of b-HPV seen in some lesions was a direct result of genome amplification within the carcinoma tissue. 34 Overall, our results indicated that E4 staining could be exploited as a marker of viral expression during b-HPVassociated skin cancer progression as reported in the HPV8 transgenic mouse model and in cervical disease for the a-genotypes. 33,[45][46][47] To extend the data obtained so far in epidermodysplasia verruciformis patients to other groups of patients at high risk of developing skin cancer, here we studied a series of skin lesions from kidney transplant recipients attending our University Hospital by systematically analyzing for the presence of b-HPV infection both at the DNA (PCR) and protein level.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…In addition, we have also demonstrated, using fluorescent in situ hybridization (FISH), that the abundance of b-HPV seen in some lesions was a direct result of genome amplification within the carcinoma tissue. 34 Overall, our results indicated that E4 staining could be exploited as a marker of viral expression during b-HPVassociated skin cancer progression as reported in the HPV8 transgenic mouse model and in cervical disease for the a-genotypes. 33,[45][46][47] To extend the data obtained so far in epidermodysplasia verruciformis patients to other groups of patients at high risk of developing skin cancer, here we studied a series of skin lesions from kidney transplant recipients attending our University Hospital by systematically analyzing for the presence of b-HPV infection both at the DNA (PCR) and protein level.…”
supporting
confidence: 72%
“…[30][31][32] In these patients, HPV5 and 8 replicate very efficiently and reveal their full transforming potential, inducing multiple cutaneous neoplasia. 33,34 Emerging evidence also supports the role of b-HPV in skin cancer development in immunosuppressed individuals. Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients.…”
mentioning
confidence: 92%
“…Exceptionally high loads of up to more than 400 viral DNA copies per cell were detected in eyebrow hair follicles of patients with epidermodysplasia verruciformis, who have a high risk of SCC development (19). The viral loads in eyebrow hair follicles from the general population and from OTR span 7 orders of magnitude and are mostly extremely low but OTR are more likely to have higher loads (20).…”
Section: Introductionmentioning
confidence: 99%
“…In both their benign and malignant lesions, a broad spectrum of predominantly beta PV were found with a combined prevalence of 90% for HPV 5 and 8 in SCC [2,6] . In lesions of EV patients, the viral genome usually persists extrachromosomally and in high copy numbers (100-300 copies per cell equivalent) [45][46][47]. High viral loads have also been found in hair bulbs from plucked eyebrows of these patients [47].…”
Section: Cutaneous Oncogenesis -Ev and Non-evmentioning
confidence: 99%
“…In lesions of EV patients, the viral genome usually persists extrachromosomally and in high copy numbers (100-300 copies per cell equivalent) [45][46][47]. High viral loads have also been found in hair bulbs from plucked eyebrows of these patients [47]. In both immunocompetent and immunosuppressed non-EV patients these viruses are also frequently found; however, only very low copy numbers (usually below one copy per cell) were detected in actinic keratosis, SCC, basal cell carcinoma, and perilesional skin [48].…”
Section: Cutaneous Oncogenesis -Ev and Non-evmentioning
confidence: 99%